Fatigue Damage Assessment of the Engine Mount Bracket Using a Statistical Based Approach - Zakaria, Kamarul Ariffin (2011)
Fatigue damage assessment is very important in design process of the component to determine their durability under service loading conditions. In service, the great majority of structures and components are subjected to stress of variable amplitude loading. The purpose of this research is to analyse statistically of two types of strain signals from road loading and compare their effect on fatigue damage of the engine mount bracket. Strain gauges were attached to the engine mount bracket and were connected to the data acquisition set in order to capture the actual strain signals when an automobile was driven on two different road surfaces. The strain signals were then analysed using global signal statistic and integrated kurtosis based algorithm for Z-filter (I-kaz) method. Meanwhile, damage of the engine mount bracket was evaluated using finite element commercial software. From the analysis, it was found that the fatigue damage showed an increment with the respective statistical values of the strain signals.